Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1111/j.1349-7006.1999.tb00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cisplatin Sensitivity in High Mobility Group 2 cDNA‐transfected Human Lung Cancer Cells

Abstract: To elucidate the role of high mobility group 2 protein (HMG2) in cis‐diamminedichloroplatinum (II) (cisplatin, CDDP) sensitivity, we constructed a human HMG2‐transfected human non‐small cell lung cancer cell line, PC‐14/HMG2. The HMG2 mRNA expression level was approximately twice those of parental PC‐14 and mock‐transfected PC‐14/CMV. Gel mobility shift assay revealed a CDDP‐treated DNA‐protein complex in the nuclear extract of PC‐14/HMG2, which was not found in the extracts of PC‐14 and PC‐14/CMV. This comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…Consistent with this notion, hormone-induced HMGB1 up-regulation in MCF-7 breast cancer cells correlates with enhanced cisplatin sensitivity (27). Increased cisplatin sensitivity was also observed in a lung adenocarcinoma cell line transfected with a plasmid expressing HMGB2, a protein with more than 80% identity to HMGB1 (28). A recent study, however, showed that loss of NHP6A, an abundant HMG box protein in Saccharomyces cerevisiae, sensitized yeast to cisplatin, suggesting that a mechanism other than repair shielding was in effect in the yeast system (29).…”
supporting
confidence: 63%
“…Consistent with this notion, hormone-induced HMGB1 up-regulation in MCF-7 breast cancer cells correlates with enhanced cisplatin sensitivity (27). Increased cisplatin sensitivity was also observed in a lung adenocarcinoma cell line transfected with a plasmid expressing HMGB2, a protein with more than 80% identity to HMGB1 (28). A recent study, however, showed that loss of NHP6A, an abundant HMG box protein in Saccharomyces cerevisiae, sensitized yeast to cisplatin, suggesting that a mechanism other than repair shielding was in effect in the yeast system (29).…”
supporting
confidence: 63%
“…Depleting HMG1 and HMG2 from cell extracts by immunoprecipitation enhanced excision repair of cisplatin-modified DNA (22). Furthermore, introducing HMG2 by transfection enhanced the cisplatin sensitivity of a lung adenocarcinoma cell line (23). Until the present work, however, there was, to our knowledge, no evidence that overexpression of an HMG domain protein via a natural signal transduction pathway in human cancer cells could increase their sensitivity to cisplatin.…”
mentioning
confidence: 53%
“…These results indicate that HMGB2 may exert a role as an antiapoptotic oncoprotein in HCC. On the other hand, the introduction of HMGB2 gene into human lung cancer cells increased cisplatin sensitivity (26), indicating that the role of HMGB2 might be dependent on types of cancer. HMGB2 suppressed the transcriptional activity of p53 in osteosarcoma (27), whereas HMGB2 enhanced the transcriptional activity of p53 in E6-positive cervical cancer, HeLa (22).…”
Section: Discussionmentioning
confidence: 99%